Factors Affecting Coffee Certification Among Rural Farm Households in Nepal - Poudel, H.K.; Kattel, R.R.; Poudel, M.R.; Khanal, S. (International Journal of Applied Sciences and Biotechnology, 2019)
The study on value chain analysis of coffee was conducted in Palpa and Kaski districts, Nepal during June to August, 2016. The purposive and random sampling technique were used. Semi-structural interview with 160 households (HH) from Kaski and Palpa district (80 samples HH from each district) were conducted. In Palpa district, third party organic certification of coffee has been adopted from company initiation, whereas all coffee from Kaski district has gone through conventional market chain. The coffee cultivated land was 0.85 ropani which was higher among non-certified group (Kaski district) as compared to certified once (Palpa district). Average price of fresh cherry was NRs. 80 per kg which was lower for company initiative third party certification in Palpa (NRs.75/kg) than non-certified area in Kaski (NRs. 85/kg). Average productivity of coffee in study area was found 48 kg per ropani which was very less (13.05 kg/ropani) in certified area than non-certified area (82.96 kg/ropani). The low productivity of coffee and weak value chain structure of coffee was found in third party certified and conventional market chains. Education (49%) and access to credit (67%) were major contributing factors for organic certification of coffee. The land for coffee cultivation had positive and significant impact whereas private company based certification had negative impact on income from coffee subsector. Effective monitoring and premium assessment from certification scheme need to have judged from concerned stakeholders to increase the benefit from certification, to promote proper certification and in coffee market chain in Nepal. Int. J. Appl. Sci. Biotechnol. Vol 7(1): 69-74